Wireless Internet Connectivity for Binabalian, Bolinao, Pangasinan (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2019)
Living in rural areas often means a lack of Internet access. The lack of access directly impedes their capability to gain the benefit of the cultural and entrepreneurial opportunities provided online. This study developed the wireless internet connectivity for Binabalian, Bolinao, Pangasinan using network standards and protocols in putting up a satellite tower. The descriptive research design was used in determining the environmental profile of the barangay in terms of geography and available ISPs as well as the testing of the wireless internet connectivity. T-test and ANOVA were used in interpreting the results gathered from the testing of the network design. The test results revealed that it supplies the necessary bandwidth requirements of the clientele and it is applicable in the barangay.
Keywords: network design, network test, wireless internet connectivity